2019
DOI: 10.1002/uog.20227
|View full text |Cite
|
Sign up to set email alerts
|

Heated humidified carbon dioxide for partial uterine insufflation in fetoscopic myelomeningocele repair: insights from animal model

Abstract: https://obgyn.onlinelibrary.wiley.com/doi/10.1002/uog.20180

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…The potential for fetal acidosis from CO 2 based on ovine model observations is one of the major concerns with fetoscopic OSB closure [31][32][33][34]. However, partial insufflation with heated, humidified CO 2 appears to lessen both fetal acid base changes [35,36] and the inflammatory reaction in the peritoneum and fetal membranes that may contribute to SROM compared to cold, dry CO 2 [36][37][38]. For these reasons, we switched to heated humidified CO 2 .…”
Section: Discussionmentioning
confidence: 99%
“…The potential for fetal acidosis from CO 2 based on ovine model observations is one of the major concerns with fetoscopic OSB closure [31][32][33][34]. However, partial insufflation with heated, humidified CO 2 appears to lessen both fetal acid base changes [35,36] and the inflammatory reaction in the peritoneum and fetal membranes that may contribute to SROM compared to cold, dry CO 2 [36][37][38]. For these reasons, we switched to heated humidified CO 2 .…”
Section: Discussionmentioning
confidence: 99%
“…11-15, 28, 29 More recent animal studies demonstrated that using heated, humidified gas may mitigate the fetal acid-base disturbances secondary to CO 2 insufflation. 16,28,29 As hypothesized by Amberg et al, heating CO 2 gas reduces its solubility while humidification reduces the intra-amniotic partial pressure of CO 2 , due to the contribution of water vapor pressure. 28 In combination, these alternations may lead to reduced absorption of CO 2 in fetuses exposed to heated, humidified gas.…”
Section: Resultsmentioning
confidence: 98%
“…Perioperative characteristics of the cases are displayed in Table 1. Maternal age was 32 (28)(29)(30)(31)(32)(33)(34)(35)(36) There were no instances of significant procedural complications, including fetal or maternal bleeding, need for emergent cesarean delivery, or fetal death. During the procedure, 2 (28.6%) cases had brief episodes of fetal bradycardia detected, both of which lasted less than 15 seconds.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Heated and humidified CO 2 gas for partial amniotic carbon dioxide insufflation is used in an attempt to decrease the risk of membrane desiccation and inflammation with subsequent membrane weakening. 142,[145][146][147] Recent animal and human data suggest safety without evidence of fetal acidemia by fetal umbilical vein sampling, including a series of seven patients who underwent percutaneous fetoscopic spina bifida repair. [148][149][150] In addition, CO 2 exposure in utero does not appear to adversely affect postsurgical fetal or postnatal growth.…”
Section: The Percutaneous Fetoscopic Technique Is Per-mentioning
confidence: 99%